Improving Lithium‐Ion Diffusion Kinetics in Nano‐Si@C Anode Materials with Hierarchical MoS2 Decoration for High‐Performance Lithium‐Ion Batteries. Issue 7 (15th February 2021) - Ye, Xiongbiao; Gan, Chuanhai; Huang, Liuqing; Qiu, Yiwei; Xu, Ying; Huang, Liuying; Luo, Xuetao
Abstract: A carbon layer on a silicon anode not only acts as a structural buffer to alleviate the tremendous volume expansion of silicon, but also enhances electrical conductivity. However, the carbon layer cannot improve the diffusion kinetics of Li + . Molybdenum disulfide (MoS2 ) nanosheets are introduced on the outermost layer of yolk‐shell silicon@carbon to design urchin‐like hierarchical anode materials, which is of great benefit in structural stability. By contrast with the yolk‐shell silicon@carbon structure, the diffusion coefficient of Li + is improved, with 3.27 times greater performance during the delithiation processes and 2.04 times greater during the lithiation process with urchin‐like hierarchical structure, showing robust diffusion kinetics. Moreover, the MoS2 nanosheets are able to enhance the delithiation reversibility of Li15 Si4 alloy formed during lithiation process. Because the MoS2 nanosheets promote the structural stability, delithiation reversibility, and diffusion kinetics of Li + during lithiation/delithiation processes, the prepared hierarchical Si@C@MoS2 composites exhibit a high reversible specific capacity of 1025 mAh g −1 with a capacity retention of approximately 81 % after 400 cycles at a current density of 1000 mAh g −1, and the reversible specific capacity can reach 819 mAh g −1 even under a high rate of 5000 mA g −1 . Abstract : Top performance : An urchin‐like structured Si‐based material is used as a high‐performance anode material for lithium‐ion batteries, which have excellent mechanical performance and efficient electron‐/ion‐transport channels, exhibiting outstanding electrochemical performances. The reasons for the excellent electrochemical performance are investigated by the delithiation behavior of the Li15 Si4 alloy and the lithium‐ion diffusion coefficient.